Characteristics of inorganic matter from Australian municipal solid waste processed under combustion and gasification conditions. Issue 7 (July 2021) - Ilyushechkin, Alexander; He, Chong; Hla, San Shwe
The presence and composition of ash in solid waste streams produced by the thermochemical processes can affect the further disposal or use of the waste. This study characterised the chemical species, mineralogy and trace element mobilisation in laboratory-produced ashes arising from different municipal solid waste (MSW) streams processed under reducing and oxidising atmospheres. The composition of cumulative ash samples produced under oxidising conditions was very similar to the composition of the industrial bottom ash samples produced during MSW incineration. We identified differences in mineral phase compositions and in some trace element concentrations of ashes produced under combustion and gasification conditions. Differences in concentrations of boron, barium, cadmium, chromium, copper, chlorine, molybdenum, antimony, lead, thorium and zinc in ashes associated with different MSW streams were also observed. On the basis of the concentrations of trace elements in ashes, we evaluated each MSW stream in terms of potential management strategies and use of the mineral matter remaining after combustion and gasification. Most of ashes produced from MSW can be at least classified as Class IV (secure) waste according to an Australian standard regulation guideline.